Stigma Wanita dengan Status Janda yang Bekerja Namun Berada dalam Lingkungan Masyarakat Penganut Paham Patriarki - Widia, Yolanda Fitri (Verdict: Journal of Law Science, 2023)
The stigma against women with widow status who work in a society that adheres to the idea of partisanship is a very important and profound legal and social issue. The purpose of this study is to identify what forms of stigma are experienced by women who have been divorced but are still working, as well as analyze the impact on their legal and social status. This study uses normative juridical methodology, legislative approaches and conceptual analysis of relevant legal materials. The data was obtained through a review of literature and academic journals related to women’s protection and social stigma. Based on the results of the study, it shows that women with a hundred divorces and working days often receive discrimination in the workplace and social environment of the community, which results in a decrease in self-confidence, mental health and reduces the opportunity to achieve economic independence and indicates an injustice in legal protection for divorced women. This study recommends the existence of education and awareness in society in reducing stigma and increasing legal protection for widowed women. As well as emphasizing the importance of changing social perceptions of widows in order to create a more inclusive and supportive environment.